The Effect of Geological Heterogeneity and Groundwater Table Depth on the Hydraulic Performance of Stormwater Infiltration Facilities - D’Aniello, Andrea; Cimorelli, Luigi; Cozzolino, Luca; Pianese, Domenico (Water resources management, 2019)
Urbanization has led to a substantial change in the hydrological cycle of urban catchments. Increased runoff and urban flooding, decreased direct subsurface infiltration and groundwater recharge, deterioration of water quality are among the major effects of this alteration. To alleviate these effects, Low Impact Development (LID) practices have been frequently adopted for stormwater management. Among LID infrastructures, infiltration facilities are particularly challenging to design and model due to the considerable amount of uncertainties related to the hydrogeological configuration of installation sites. To date, analysis on how soil heterogeneity, groundwater table depth, and thickness of the unsaturated zone affect the hydraulic performance of infiltration facilities are lacking. To address this knowledge gap, a series of numerical experiments under transient variably water saturated conditions were performed for a hypothetical infiltration facility. Numerical simulations showed that i) infiltration rates increase considerably as the initial depth of the groundwater table increases, ii) the contribution of the bottom of the facility to the infiltration of water is generally higher than the sides, iii) the presence of a less conducting soil layer at a short depth from the bottom of the facility reduces infiltration rates dramatically, iv) the complete clogging of the bottom of the facility has a dramatic impact on the hydraulic performance, v) the stochastic heterogeneity of the soil controls the overall stormwater infiltration process through the facility, and the hydraulic performance may largely deviate from the case when heterogeneity is absent.